Początki koncepcji natchnienia biblijnego w dyskursie religijnym - Baraniak, Marek (Colloquia Litteraria, 2022)
The category of “Biblical inspiration” dates back to the biblical period. Subsequently, the early Jewish and Christian traditions made many attempts to describe it definitively. Over the centuries, many ways have emerged to understand the nature of the inspiration and to explain its relationship to the human author. One difficulty is the overly simple understanding of the inspiration model of the prophetic texts in the Bible.